How pilot free trade zones affect food system resilience: quasi-natural experiment evidence from China - Zeng, Huasheng; Zhang, Bianhao; Yan, Yue; Huang, Chunyan (Frontiers in Sustainable Food Systems, 2025)
IntroductionEnhancing the resilience of food systems is of paramount importance when faced with frequent and uncertain shocks. As pioneering zones for advancing reform and opening up in China, the pilot free trade zones provide a unique perspective for studying the impact on food system resilience. The existing literature rarely explores the mechanisms of improving food system resilience from the perspective of pilot free trade zones. Therefore, this study used the implementation of China’s pilot free trade zones as a quasi-natural experiment to analyze the impact on food system resilience and its mechanisms.MethodsThis study initially resolves the problem of selection bias by employing the propensity score matching (PSM) method, and then estimates the extent of the impact of pilot free trade zones on food system resilience through the staggered differences-in-differences (staggered DID) method, finally examining the mechanisms by which pilot free trade zones affect food system resilience using the mediation effect model.Results and discussionPilot free trade zones can promote food system resilience. Rural human capital and agricultural technological innovation were crucial channels through which pilot free trade zones enhanced food system resilience. From the perspective of heterogeneity, the implementation of pilot free trade zones primarily enhances the innovation capability of the food system resilience, in contrast to its resistance and recovery capabilities. Additionally, the pilot free trade zones have a stronger promoting effect on coastal areas compared to inland regions of China. Furthermore, these zones have a greater enhancing effect on the western regions of China, compared to the eastern and central regions. Finally, the pilot free trade zones demonstrate a more pronounced effect on enhancing non-grain-producing areas compared to major grain-producing regions.ConclusionTo achieve synergistic development for high-quality construction of pilot free trade zones and food system resilience, it is necessary to promote high-quality construction of pilot free trade zones, enhance rural human capital, and agricultural technological innovation.